The Influence of Digital Halal Influencers on the Purchase Decision of Halal Products among Generation Z - Desty Prawatiningsih Desty; Fahma Islami; Siti Yuliyanti (Golden Ratio of Marketing and Applied Psychology of Business, 2027)
The expansion of digital halal marketing has increased the role of digital halal influencers, who not only promote products but also communicate religious messages and halal-related values to Muslim consumers. This study examines the effects of audience engagement, halal value, and influencer credibility on halal product purchase decisions among Muslim Generation Z in Indonesia. It also investigates whether influencer credibility mediates the effects of audience engagement and halal value on purchase decisions. Data were collected through a cross-sectional online survey administered using Google Forms. The final sample consisted of 210 Muslim Generation Z students from the Faculty of Da’wah at UIN Sultan Maulana Hasanuddin Banten, selected through convenience sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 3.0. The results show that audience engagement positively and significantly affects influencer credibility and purchase decisions. Halal value also positively and significantly affects influencer credibility and purchase decisions. However, influencer credibility does not have a significant effect on purchase decisions and does not mediate the relationship between audience engagement and purchase decisions or between halal value and purchase decisions. The model explains 53.5% of the variance in influencer credibility and 45.0% of the variance in purchase decisions. These findings identify a contextual boundary of Source Credibility Theory by demonstrating that influencer credibility alone may be insufficient to generate purchasing responses among Muslim Generation Z. Meaningful digital engagement and clear halal value appear to be more influential than the personal credibility of influencers. The findings imply that halal businesses should prioritize interactive communication, transparent halal information, and value-consistent content rather than relying solely on influencer popularity or reputation.